Perception of Virtual Education Learning among Dental Residents and Faculty during the COVID-19 Pandemic: A Cross-Sectional Study - Shasha Cui; Kumari Saswati Kar; Shruti Vasani; Nisreen Al Jallad; Mechelle R. Sanders; Rita Cacciato; Tong Tong Wu; Jin Xiao; Hans Malmstrom (MDPI AG, 2024)
Objectives: The coronavirus disease 2019 (COVID-19) pandemic prompted a rapid shift from in-person to virtual learning in dental education. This study aims to assess the perceptions of virtual education learning among dental residents and faculty and employ regulatory focus theory (RFT) to understand the impact of motivational orientations on virtual learning during the COVID-19 pandemic. Methods: In total, 46 dental residents and 10 faculty members in a dental institution participated in the study (June-August 2021). Questionnaires were used to obtain data on demographics, perceptions of virtual learning, burnout, and RFT types (promotion and prevention focus). Multiple regression analyses were used to examine factors associated with perceptions of virtual learning and burnout. Results: Overall, 70% of residents and 44% of faculty found virtual learning effective. Younger residents with less experience preferred virtual learning more than their older, experienced peers. Residents trained outside the U.S. and Canada favored in-person learning more than those trained within. Furthermore, residents with a higher promotion focus score found virtual learning more interactive for didactic courses. Additionally, 52% of residents experienced burnout, with a higher incidence among females (p = 0.044). Conclusions: Virtual learning is well received by dental residents and faculty, with potential for continued use post-pandemic. Future efforts should focus on creating an inclusive and supportive educational environment that meets the motivational and well-being needs of dental residents and faculty.